MENERAPKAN MODEL PEMBELAJARAN QUANTUM TEACHING UNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAM KETERAMPILAN MENULIS KARANGAN NARASI DI KELAS V SD DHARMA WANITA PERTIWI MEDAN TAHUN PEMBELAJARAN 2017/2018 - SILALAHI, INDAH AYU IRWINA (Jurnal Ilmiah Aquinas, 2018)
TAHUNNYA 57MENERAPKAN MODEL PEMBELAJARAN QUANTUM TEACHINGUNTUK MENINGKATKAN HASIL BELAJAR SISWA DALAMKETERAMPILAN MENULIS KARANGAN NARASIDI KELAS V SD DHARMA WANITA PERTIWI MEDANTAHUN PEMBELAJARAN 2017/2018OLEH:INDAH AYU IRWINA SILALAHI(PGSD FKIP UNIVERSITAS KATOLIK SANTO THOMAS SU)ABSTRACTThis study aims to describe the study of class action research (PTK)using the model of learning quantum teaching on the subjects of Indonesialanguage in class V SD Dharma Women Pertiwi Medan. The research approachused is qualitative approach with the subject of research, that is, students of classV SD Dharma Women Pertiwi Medan, especially VB class which amounted to 24people. Data collection technique used are observation and test. The main datasource of this research is primary data. Primary data sources were obtained fromteachers and students in grade V SD Dharma Woman Pertiwi Medan. The resultsof the research in the first cycle obtained by observation of teacher activity 54%,observation of student activity 55%, and complete according to value MinimumExhaustiveness Criterion (KKM) is 10 people with percentage 42%, whileunfinished 14 students with percentage 58,3% from a total 24 students. Theaverage score of students in the first cycle was 60,75. Students who complete theclassical has not reached 75%, then continued in the next cycle. In the secondcycle, the result of observation of the teacher activity is 94%, the observationresult of student activity is 82,5%, and that is complete according to KKM value22 people with percentage 92%, while 2 students wit unfinished percentage 8,3%from 24 students. The average value of cycle II is 87,75. Based on the dataanalysis it can be concluded that the application of the model of learning quantumteaching to improve the learning outcomes In Skills Creating Narrative Essay InStudents Class V Sd Dharma Women Pertiwi Medan Year Learning 2017/2018has both categorized and student learning outcomes increased. Limitations of thisresearch is a model of learning Quantum Teaching is a model of learning thatinvites students to be more focused and creative in writing a good articlenarrative. Based on the results of this study suggested to elementary schoolteachers to be more creative in implementing the model of learning QuantumTeaching on the learning process.